Pengaruh Normasi Kelompok terhadap Efektivitas Team Work di SMA Muhammadiyah 2 Kertosono - A Wathon; Prim Masrokan Mutohar; Imam Fuadi (Lembaga Yasin AlSys, 2025)
The limited number of in-depth studies on group norming dynamics and their implications for team effectiveness in secondary education settings—particularly in faith-based institutions such as SMA Muhammadiyah 2 Kertosono—serves as the background for this research. This phenomenon is crucial to examine, as it directly influences the achievement of collaborative learning goals, the development of social skills, and the formation of Islamic character in line with the school's vision. The study aims to comprehensively analyze the formation process of group norms, the mechanisms through which students internalize these norms, and their impact on team effectiveness. A qualitative approach was employed using an intrinsic case study design, allowing for an in-depth exploration of participants’ subjective experiences. The findings reveal that group norms emerge through repeated social interactions, are driven by religious values and school culture, and are reinforced by peer monitoring within teams. Both explicit and implicit norms contribute to patterns of communication, motivation, and team cohesion, directly affecting the effectiveness of collaborative task completion. These results support social identity theory and social learning theory in explaining the role of norms in group dynamics. Theoretically, this research contributes to the literature on group dynamics in Islamic educational contexts. Practically, it recommends that schools and educators develop intervention strategies to foster the formation of positive and constructive group norms. Furthermore, the study opens avenues for future research on student leadership roles and the impact of group norming on psychological well-being in secondary education environments.